AN ENSEMBLE ONE-DIMENSIONAL CONVOLUTIONAL NEURAL NETWORK WITH BAYESIAN EXPONENTIAL ADAPTIVE GRADIENTS FOR SOUND CLASSIFICATION - RAGAB, MOHAMMED GAMAL (2021)
With the growth of deep learning in various classification problems, many researchers have used deep learning methods in environmental sound classification tasks.